(untitled) (Laisvalaikio tyrimai, 2018)
Research background. Ethics covers various areas of life: personal, public and professional relations. Personal ethics studies the well-being of certain individual and their development methods. Social ethics emphasizes well-being of society, duties of individual persons in the society. In the professional ethics the main attention is paid to the behaviour of the representatives of a special field (Raipa, 2001). Employees working in public sector inevitably stick with ethic and working culture problems. Perhaps even more often than the representatives of other fields because they constantly communicate with people, help them to solve their problems every day, inform people about new products (Wagner-Tsukamoto, 2005). When having some contact with employees, people judge the morality and working culture of higher officers and the whole sector according to their behaviour (Chen, 2005). Therefore ethics and working culture of public sector employees should be as high as possible. Ethics is important not only in communication with customers (external environment), it is also important internally in the organization, in the mutual relations between colleagues and staff members (Palidauskaite, 2001). Ethical problems might cause different consequences. Some of them are solved almost unnoticed; the others have strong impact on persons or organizations. Ethical problems might occur and disappear or have a continuous character. The purpose of the work was to disclose the importance of ethics and working culture of the employees in the Klaipėda municipality sector. Object of the work was ethics and working culture of the employees. Methods. In this paper we used analysis of scientific literature, analysis of legislation, questionnaire survey, statistical analysis of the data, graphical modelling, specifying and summarizing, and logical abstraction methods. We also analysed scientific and practical materials of national and foreign authors (Raipa, 2001; Palidauskaitė, 2001; Chen, 2005; Fassin, 2005). In order to disclose the importance of ethics and working culture of the employees we chose municipality of Klaipeda region for the research. Conclusions. Organizations are unlikely to have just a single overarching culture. Instead, multiple cultures or subcultures are often present. Organizational cultures are shared experiences resulting from both low-and high profile successes and failures, patterns of conduct, and selfregulating practices. Ethics and working culture in the work of public sector are nonetheless important than in the work of other professions because they have to communicate with people every day. Work culture change is a process of giving and taking by all members of an organization. Formalizing strategic direction, systems development, and establishing measurements must be owned by the group responsible for them. Conflicts in the work of public sector are the negative appearance because of their negative impact on the person itself and the people around - customers, colleagues. It has a negative impact on the efficiency of work, communication, working atmosphere. The employees of Klaipeda municipality who participated in the survey agreed with the opinion that the standards of ethics applicable to the public officers are stricter than those applied to ordinary citizens and also the proper image of the employee helps to support public confidence in service. Keywords: working culture, ethics, employees, public sector.